The storage space allocation problem in a dry bulk terminal: a heuristic solution. Issue 2 (2020) - Ouhaman, Assia Ait; Benjelloun, Khalid; Kenné, Jean Pierre; Najid, Najib
Abstract: The bulk port operations are given a growing attention for their important role in the global supply chain in different industries (mining, energy ...). To guarantee their competitiveness, the efficient management of port logistics, including yard side management is crucial. In this paper, we consider a real-word storage space allocation problem at an export bulk terminal. We formulate the problem as a mixed integer linear program and we propose a heuristic method to solve large scale data sets. Both the model and the heuristic can help the yard planner to test different scenarios and provide better stock yard plan, which is a first step toward improving the management of port operation in the bulk terminal under study.